Toksisitas Sub Akut Ekstrak Etanol Daun Kemangi (Ocimum sanctum L.) Terhadap Fungsi Hati dan Ginjal Pada Mencit Putih Jantan - Ifora Ifora; Helmi Arifin; Diana Idrifa (Jurnal Farmasi Higea, 2015)
Sub-acute toxicity testing of the ethanol extract of basil leaf  (Ocimum sanctum L.) has been done to the liver and kidney function male white mice. This testing includes checks alanine aminotransferase activity, serum creatinine levels and the relative weight of organs (liver and kidney). Extract administered orally at a dose variation of 100 mg/kg, 200 mg/kg and 400 mg/kg for 7, 14 and 21 days. The results showed basil leaf extract at a dose of 100, 200 and 400 mg/kg no significant effect on the activity of SGPT, serum creatinine levels and relative organ weight (p > 0.05).